2020
DOI: 10.1111/omi.12302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Porphyromonas gingivalis and Fusobacterium nucleatum on inflammasomes and their regulators in H400 cells

Abstract: IntroductionInflammasomes are multiprotein complexes that regulate immune processes in response to infections and tissue damage. They modulate Interleukin‐1beta (IL‐1β) expression, a major proinflammatory cytokine. The inflammasome/IL‐1β pathway is involved in head and neck squamous cell carcinoma (HNSCC) progression and the periodontal pathogens Fusobacterium nucleatum (Fn) and Porphyromonas gingivalis (Pg) have been reported to cause chronic inflammation in HNSCC. The aim of this study was to characterise th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…28,29 In particular, oral bacteria including Porphyromonas gingivalis, Fusobacterium nucleatum and Treponema denticola have been recognized as potential etiological agents of oral cancer and recently these pathogens have been found to dysregulate inflammatory mechanisms in oral cancer cells. 30,31 Certain limitations should be considered when interpreting the results of the present study. First, the dietary habits of the subjects were not considered in our study.…”
Section: Discussionmentioning
confidence: 91%
“…28,29 In particular, oral bacteria including Porphyromonas gingivalis, Fusobacterium nucleatum and Treponema denticola have been recognized as potential etiological agents of oral cancer and recently these pathogens have been found to dysregulate inflammatory mechanisms in oral cancer cells. 30,31 Certain limitations should be considered when interpreting the results of the present study. First, the dietary habits of the subjects were not considered in our study.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have found that extracellular ATP can activate T cells expressing P2 × 7, inhibit the differentiation and function of regulatory T (Treg) cells, and induce them to differentiate into TH17 cells and promote the production of interleukin-17 (IL-17) in white blood cells [157,158]. Meanwhile, ATP can also promote the activation of NLRP3 inflammasome in phagocytes, thereby releasing a large amount of IL-1 and IL-18, further aggravating the occurrence of inflammation [159]. In fact, extracellular ATP also has a regulatory effect on the functions of CD4 + T cells and Treg cells, and this regulation is concentration-dependent [160].…”
Section: Atpmentioning
confidence: 99%
“…IL-1β plays a pro-tumorigenic role and enhances the aggressiveness of OSCC [ 66 ]. Aral et al reported that F. nucleatum infection in OSCC cells promotes AIM2 inflammasome expression [ 67 ]. In addition, F. nucleatum potentially upregulated IL-1β expression, but downregulated POP1 which controls NLRP3 inflammasome activation by targeting ASC.…”
Section: F Nucleatum and Cancermentioning
confidence: 99%